Schwannoma of upper eyelid: A rare differential diagnosis of eyelid swellings - Surendra B. Patil; Satish M. Kale; Sumeet Jaiswal; Nishant Khare (Indian Journal of Plastic Surgery)
Schwannoma is a relatively rare benign tumour of peripheral nerve origin. The occurrence of Schwannoma in eyelid is extremely rare. As per our knowledge, only 11 such cases have been reported in the literature so far. We present a case of a 40-year-old man who presented to us with a 2-year history of slowly enlarging, painless mass in his left upper lid with resultant progressive ptosis. Ocular examination was suggestive of a firm, non-tender nodule of size 2 × 1.5 × 1 cm on the left upper lid. The mass was non-adherent to the skin or the underlying tissue. The eyelid skin and conjunctiva were indurated and signs of inflammation were present. The lateral part of eyelid showed presence of an ulcer and the lid function was severely hampered. Provisional clinical diagnosis was that of an eyelid malignancy. With this in mind, the medial part of the lid was excised and reconstructed using a tarso-conjunctival flap from the lower eyelid in conjunction with a skin graft. The histopathology and immunohistochemistry established the diagnosis of Schwannoma. We recommend that Schwannoma be considered in the differential diagnosis of well-circumscribed eyelid swellings.